Estudio de factibilidad para la creación de un punto para la comercialización de helados en el municipio de El Carmen de Viboral, Antioquia (2020)
The business idea aiming to position this company in the municipality of Carmen de Viboral, eastern Antioquia, arose obligation to inquire for new market niches. For the reason above, the aim was to inquire about the potential market to position ice-cream business Los Monjes Ice Cream Parlor in El Carmen de Viboral municipality. It was consulted which is the state demand of the ice cream and fruit salad sectors. Drawing from these data, we formulated the enter strategy to position Los Monjes Ice Cream Parlor in El Carmen de Viboral, Antioquia, as a company engaged in the sale of varied types of ice cream, and the preparation of fruit salads that provide added value in their flavor, service, and quality. Each research line is backed by analyses and studies, which bring about the development of new strategies and aims to accomplish the consolidation of Los Monjes Ice Cream Parlor, acceptance and enjoyment looking to achieve competitive success in the town of El Carmen de Viboral, Antioquia.